Developing augmented reality on differential system, competency system, and power transfer in vocational education - Dandi Firman Dani; Sulaeman Deni Ramdani; Deddy Supriyatna (Jurnal Pendidikan Vokasi, 2022)
This study aimed to know: 1.) Describe the development of augmented reality books in the differential system; and 2.) Analyze the feasibility level of the application on the augmented reality book differential system. This study uses research and development (R&D) with the waterfall development design model, which includes four stages: analysis, design, coding or implementation, and testing. This study's sample was 11th-grade vocational high school students majoring in automotive light vehicle engineering. Application testing uses black-box testing by testing functionality without testing the internal structure or function of the application. The data collection used in this study included three media experts, three material experts, and 30 user responses (students) with data analysis techniques using descriptive analysis. The results of this study are (1) augmented reality books and applications on the android platform as learning media on the differential system, and (2) feasibility analysis by media expert validation with an average value of 80%, material experts with an average value of 84% and user responses with an average value of 90 % with a total value of 85% with the 'very eligible' category to be used as a learning medium in the differential system of chassis and power transfer competencies. Research products can be used as an attractive alternative learning media by utilizing digital technology that can display 3D objects in detail on the competence of the differential system.